The influence of person-organization fit on employee engagement: Psychological contract as a mediating effect in Thailand's logistics industry - Khahan Na-Nan; Kanakarn Phanniphong; Nutt Jaturat; Natnarong Jaturat; Malee Jaturat (Acta Psychologica, 2025)
This study examines the influence of person-organization (PO) fit on employee engagement (EE) within Thailand's logistics industry, emphasizing the mediating role of a psychological contract (PC). As the logistics sector undergoes rapid growth, aligning employees' values with organizational priorities is becoming critical. Employees with a high PO fit are likely to exhibit positive attitudes and behaviors, contributing significantly to organizational success. This research investigates the extent to which a PC, representing mutual expectations and obligations, mediates the relationship between PO fit and EE. Structural equation modeling was used to analyze data collected from 400 employees across various logistics firms in Thailand to test the proposed hypotheses. Our findings show that a strong PO fit enhances EE, both directly and indirectly, through a positive PC characterized by trust and fairness. The results suggest that fostering a high PO fit and maintaining a positive PC are essential for sustaining EE and reducing turnover intentions. This study provides valuable insights for logistics firms aiming to enhance workforce commitment and performance in a competitive environment.